Business continuity planning (BCP) / Arith Syakir Bunsu ... [et al.] - Bunsu, Arith Syakir; Daniel, Nur Zafika; Ramsa, Rizwanshah; -, Siti Nur Syazwanie; Empang Wan, Veronica (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Business continuity planning (BCP) is about identifying the critical functions and services your business delivers and planning for how you would maintain or resume them in any disruptive event or emergency (such as a power outage, fire, flood or earthquake). After all, if you can't deliver your critical functions and services:Clients, staff and suppliers could be adversely affected. Customers might look elsewhere and turn to your competitors. You may fail to meet contractual or legislated obligations. There may be financial repercussions. Your organisation's reputation could be adversely affected Business continuity planning. (BCP) is about identifying the critical functions and services your business delivers and planning for how you would maintain or resume them in any disruptive event or emergency (such as a power outage, fire, flood or earthquake). After all, if you can't deliver your critical functions and services: If any of these things are important to you or your business, then you should have business continuity arrangements in place. There are many reasons to plan which is to protect your investment, protect your livelihood, legal obligations, fulfil essential services, stakeholder obligations, satisfy financial partners, take care of business reputation and meet increased demand.